Strategic Optimization of Village Cooperatives for Economic Sovereignty and Poverty Alleviation: A Case Study of Sindangpakuon Village - Fadilla, Febrynahl Fitra (Research Collaboration Community (Rescollacom), 2026)
The purpose of this study is to investigate the structural reform of economic institutions at the village level, with Sindangpakuon Village serving as the primary case study. This is done with the intention of reducing poverty. Even though Indonesia has undergone a significant amount of decentralisation, a great number of rural areas continue to be trapped in cycles of economic dependence. As a result of the widespread presence of exploitative informal lending, which is commonly referred to as